2020
DOI: 10.1002/mar.21385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two decision‐making paths underpinning the continued use of branded apps

Abstract: This study investigates two decision‐making paths that underpin the continued use of branded apps. One path originates from past use of a category of apps and leads to continued use of a branded app from that category via recognition. The second path also starts with past use, but leads to continued use through the evaluation of the app's benefits. Two empirical studies test and subsequently validate the resulting conceptual model, confirming that both paths underpin continued use; however, the strength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 94 publications
(124 reference statements)
2
17
0
Order By: Relevance
“…The relationship between the intention towards a behavior in determining the user behavior is well documented in the literature (see Ajzen, 1988, 1991; Davis et al, 1989; Taylor & Todd, 1995b; Venkatesh, Morris, et al, 2003; Venkatesh et al, 2012). Thus, building on previous conceptualizations (e.g., Bellman et al, 2011) and recent work (McLean et al, 2020; Stocchi et al, 2020), we suggest that the continuous usage intention of retail smartphone shopping apps will result in increased usage and purchase frequency. From this perspective, we hypothesize the following:…”
Section: Research Hypothesessupporting
confidence: 58%
See 3 more Smart Citations
“…The relationship between the intention towards a behavior in determining the user behavior is well documented in the literature (see Ajzen, 1988, 1991; Davis et al, 1989; Taylor & Todd, 1995b; Venkatesh, Morris, et al, 2003; Venkatesh et al, 2012). Thus, building on previous conceptualizations (e.g., Bellman et al, 2011) and recent work (McLean et al, 2020; Stocchi et al, 2020), we suggest that the continuous usage intention of retail smartphone shopping apps will result in increased usage and purchase frequency. From this perspective, we hypothesize the following:…”
Section: Research Hypothesessupporting
confidence: 58%
“…Furthermore, McLean et al (2020) while investigating technical functional aspects (e.g., usefulness, ease of use, customization) and the hedonic aspect of enjoyment in the continuous usage context of retail apps, they also examined the role of the consumer's attitude toward the app in influencing the consumer's attitude and loyalty toward the brand. In a related study, Stocchi et al (2020) investigated consumers' past experiences and its role in influencing consumers' continuous intention to use branded apps through two decision‐making paths (i.e., the app recognition path, and the evaluation of utilitarian and hedonic benefits path). More so, Fang (2019) investigated the role of the branded app value‐in‐use in influencing brand competence, brand warmth, the consumer's brand loyalty, and the continuous intention to use the app, while examining factors related to the affordances of mobile apps.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Smartphone and mobile app usage has surged further during the Covid-19 global pandemic, seeing an overall increase in smartphone usage by 20%, with spending through apps having increased by 25% from the previous year (App Annie, 2020). Research has found that a prominent reason for such extant use of mobile apps is as a distraction mechanism (Stocchi et al, 2018(Stocchi et al, , 2020. Accordingly, to escape the stresses of everyday life, and to achieve instant forms of gratification, consumers are engaging in escapism behavior, entering a flow state of mind through mobile apps.…”
mentioning
confidence: 99%